Minat Belajar Mahasiswa Dimasa Pandemi Covid-19 Terhadap Hasil Belajar Mahasiswa - saepul mustakim, usep (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2024)
The Teaching and learning activities during this pandemic are expected to be carried out well with optimal learning outcomes. The purpose of this study was to find out how much interest in student learning during the covid-19 pandemic was on student learning outcomes in the hope of increasing their learning outcomes. The method used in this research is a quantitative approach where the data is obtained by statistical tests assisted by the SPSS for windows application. The data was accumulated and analyzed by regression analysis so that after statistical calculations, a score of 61.70% was obtained, of which a value of that size could be interpreted quite well or it could be said that the learning outcomes were quite good and the student's interest in learning was also quite good.